PERCOBAAN PEMUTIHAN KULIT ROTAN SEGA (CALAMUS CAESIUS BL.) DENGAN METODA PERENDAMAN DALAM LARUTAN HIDROGEN PEROKSIDA (H2°2) - Abdul Hakim Lukman (Jurnal Penelitian Hasil Hutan, 1992)
The effects  of  bleaching  of sega rattan  (Calamus  caesius Bl) peel  by soaking  in the  hydrogen  peroxyde of  several  concentration  levels  (1 , 3,  5,  and  7 percent)  and  soaking  times  ( 1,  3,  and 5 hours)  on  rattan peel  quality   were studied  at  the  Forest  Products Research  and Development   Centre  Laboratory   in  Bogor.  Results  showed  that   the unblea- ched  rattan  peel  has the  brightness of  38.8  percent  and  the  tensile  strength  parallel to  grain  of  412.09  kg/cm2   while for the bleached  ones,  those  figures are 44. 74 percent  and 374.99  kg/cm2,   respectively.It  is found   that  bleaching  agent  concenlration   has a highly  significant  effect  on  both  brightness and tensile  strength parallel    to  grain.   The  brightness   (Y)   was significantly improved   with   the  increasing  of  bleaching  agent  concentrations (X)  which   can  be  expressed   by  the  regression  equation   of  Y  =  40.2365   + 1.1265  X  (r = 0.9992).   On the  other   hand, tensile strength   (Y)  was  significantly decreased  with  the  increasing  of hydrogen peroxyde  concentrations  (X,  as expressed by  the following rearession  equation:   Y  = 421.37 5 - 11.675 x  (r =  0.9888 ).The  apllcation  of 5 percent   hydrogen  peroxyde   concentration   is optimum  which  could improve the brightness  up to  46. 03 percent,   and  reduced  the  tensile  strength down  to 364.8  kg/cm2.